2007
DOI: 10.1039/b609200b
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent polynuclear assemblies

Abstract: This tutorial review consists of five main sections. The first gives a general introduction and then a discussion about the need for luminescent assemblies. The next four sections present the various assemblies based on the metal ions used to assemble the final structures. Each of these sections gives a brief overview of the design principles, synthesis, and ground and excited-state properties of the ligands and complexes in question. The review concludes with some suggestions for future avenues of research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(67 citation statements)
references
References 67 publications
0
67
0
Order By: Relevance
“…The nicotinato anions act as a chelating ligand as well as a bridging ligand to link the clusters thus forming the 3D polymeric structure. The metal centres have three types of coordination environment: Gd(9), Gd(12), Gd (19) and Gd (25) are nine-coordinate, while the remaining Gd atoms are eight-coordinate surrounded by μ 3 -OH, terminal water molecules, nicotinato anions and CO 3 2-ions. Four GdO x polyhedra are connected to each other to form a secondary building unit, Gd 4 , by sharing four μ 3 -OH groups, consequently, giving rise to five distorted cubane cores having the face dimensions of c.a.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nicotinato anions act as a chelating ligand as well as a bridging ligand to link the clusters thus forming the 3D polymeric structure. The metal centres have three types of coordination environment: Gd(9), Gd(12), Gd (19) and Gd (25) are nine-coordinate, while the remaining Gd atoms are eight-coordinate surrounded by μ 3 -OH, terminal water molecules, nicotinato anions and CO 3 2-ions. Four GdO x polyhedra are connected to each other to form a secondary building unit, Gd 4 , by sharing four μ 3 -OH groups, consequently, giving rise to five distorted cubane cores having the face dimensions of c.a.…”
Section: Resultsmentioning
confidence: 99%
“…The azido ion plays an important role in isolating the cluster-based compound 1. Mixing of the reactants viz., Gd(NO 3 ) 3 , nicotinic acid and sodium azido in a 1:2:2 ratio resulted a 1D chain compound of gadolinium(III) ions and EO azido bridges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] Previous reports on molecular dyads based on porphyrin and polypyridyl ruthenium(II) complex have shown that photoinduced intramolecular electron transfer and/or energy transfer can occur between the polypyridyl ruthenium(II) moiety and the porphyrin moiety. [22][23][24] However, to the best of our knowledge, the porphyrin-polypyridyl ruthenium(II) hybrid with special properties, in which the porphyrin core links to polypyridyl ruthenium(II) moiety by a flexible alkyl chain, self-assembled on HOPG have never been studied by STM in ambient conditions.…”
Section: Introductionmentioning
confidence: 96%
“…One of the most important physicochemical properties of supramolecular complexes are their luminescence properties 1 . Transition metal complexes which exhibit emission of light are attractive materials for the construction of organic light-emitting diodes 2-6 .…”
Section: Introductionmentioning
confidence: 99%